The noel stranger - Evans, Richard Paul (New York : Simon & Schuster, 2018)
"Maggie Walther feels like her world is imploding. Publicly humiliated after her husband, a local councilman, is arrested for bigamy, and her subsequent divorce, she has isolated herself from the world. When her only friend insists that Maggie climb out of her hole, and embrace the season to get her out of her funk, Maggie decides to put up a Christmas tree and heads off to buy one$1 (Balbeit reluctantly. She is immediately taken by Andrew, the kind, handsome man who owns the Christmas tree lot and delivers her tree. She soon learns that Andrew is single and new to her city and, like her, is also starting his life anew. As their friendship develops, Maggie slowly begins to trust again$1 (Bsomething she never thought possible. Then, just when she thinks she has finally found happiness, she discovers a dark secret from Andrew$1 (Bs past. Is there more to this stranger$1 (Bs truth than meets the eye?"--s
Keywords: Man-woman relationships -- Fiction; Divorced women -- Fiction; Secrecy -- Fiction; Salt Lake City (Utah) -- Fiction; Christmas fiction; Romance fiction